Analisis Kapasitas Saluran Drainase Menggunakan Program SWMM 5.1 di Perumahan Tasmania Bogor, Jawa Barat - Kartiko, Luthfi; Waspodo, Roh Santoso Budi (Departemen Teknik Sipil dan Lingkungan IPB, 2018)
The intensity and duration of rainfall will affect the amount of runoff. A proper drainage design is needed so that runoff from maximum rainfall would not cause a problem such as excess water or flood. The purpose of this research were to analyze the runoff volume in Tasmania Regency, Bogor and get drainage network design in accordance with the runoff that occured. Analysis was carried out using SWMM 5.1 software with designed rainfall was calculated using the Log-Person III method of 147.2 mm. Peak discharge runoff from simulation results were 0.01 - 0.08 m3/s. Based on the simulation there were 20 channels overflowed during maximum runoff and 6 channels were high potentially overflowed so that repairs were also needed. The factors that influenced were the amount of runoff, channels capacity were lower than runoff volume, and the low infiltration value of subcatchment so that only a little water could be infiltrated and the rest of rainfall became runoff.Keywords: drainage channel, rainfall, runoff, SWMM 5.1